On the Development of a Computer-Based Tool for Formative Student Assessment: Epistemological, Methodological, and Practical Issues - Tomasik, Martin J.; Berger, Stéphanie; Moser, Urs (Frontiers in Psychology, 2018)
Formative assessments in schools have the potential to improve students’ learning outcomes and self-regulation skills; they make learning visible and provide evidence-based guidelines for setting up and pursuing individual learning goals. With the recent introduction of the computer-based formative assessment systems for the educational contexts, there is much hope that such systems will provide teachers and students with valuable information to guide the learning process without taking much time from teaching and learning to spend on generating, evaluating and interpreting assessments. In this paper, we combine the theoretical and applied perspectives by addressing (a) the epistemological aspects of the formative assessment, with an emphasis on data collection, model building, and interpretation; (b) the methodological challenges of providing feedback in the context of instruction in the classroom; and (c) practical requirements for and related challenges of setting up and delivering the assessment system to a large number of students. In the epistemological section, we develop and explicate the interpretive argument of formative assessment and discuss the challenges of obtaining data with high validity. From the methodological perspective, we argue that computer-based formative assessment systems are generally superior to the traditional methods of providing feedback in the classroom, as they better allow supporting inferences of the interpretive argument. In the section on practical requirements, we first introduce an existing computer-based formative assessment system, as a case in point, for discussing related practical challenges. Topics covered in this section comprise the specifications of assessment content, the calibration and maintenance of the item bank, challenges concerning teachers’ and students’ assessment literacy, as well as ethical and data-protection requirements. We conclude with an outlook on possible future directions for computer-based formative assessment systems and the field in general.